Critical Thinking Ability in Solving Word Problems Based on David Kolb's Learning Style - Nur Juhainah Ulfa; Dian Permatasari (Journal of General Education and Humanities, 2023)
This study aims to describe students' critical thinking skills in solving word problems based on David Kolb's learning style. The type of research is descriptive qualitative research conducted at MAN in Bantul using purposive sampling. The data collection techniques in this study were critical thinking skills tests, learning style questionnaires, and interviews. The data analysis used is condensation, data presentation, and conclusion Drawing. The results show that students' three learning styles are diverger, assimilator, and converger. Students' critical thinking skills in divergent learning styles are medium and low. The diverger student can master the average indicators of interpretation, analysis, evaluation, inference, and explanation but cannot meet the self-regulation indicators. The student's critical thinking skills with assimilator learning style are high, medium, and low. Students with high and moderate can master all critical thinking indicators, but low assimilator students can master the indicators of interpretation, analysis, evaluation, inference, and explanation. The student's critical thinking ability with a converger learning style is medium and low. Medium converger students can master all critical thinking indicators. Low converger students can master the indicators of interpretation, analysis, evaluation, inference, and explanation but are less able to meet the self-regulation indicators.